Multiple dental retention: Case report and literature review (Research, Society and Development, 2021)
Multiple dental retention is a pathology that presents several dental organs located inside the alveolar processes of both the maxilla and the mandible. Taking into consideration that this pathology may be related to local or systemic factors that condition its presence and may be accompanied by additional pathologies, such as, in this case, dentigerous cysts. Next, the case of a 20-year-old male patient with 13 retained teeth is reported, who has a systemic disease not related to said pathology. The objective is to inform and encourage a correct anamnesis, detailed clinical and radiological analysis, which allow us to reach a correct diagnosis and a good treatment plan; in order to generate a basis for future research.